gwp 2019
DOI: 10.24149/gwp370
|View full text |Cite
|
Sign up to set email alerts
|

Oil Curse, Economic Growth and Trade Openness

Abstract: An important economic paradox that frequently arises in the economic literature is that countries with abundant natural resources are poor in terms of real gross domestic product per capita. This paradox, known as the "resource curse," is contrary to the conventional intuition that natural resources help to improve economic growth and prosperity. Using panel data for 95 countries, this study revisits the resource curse paradox in terms of oil resource abundance for the period 1980-2017. In addition, the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In this instance, it is argued that oil price fluctuations have a considerable impact on individuals’ welfare over the globe (Mgbame et al , 2015). However, other works claim that the actions of economic policies can absorb the effect of oil price shocks on the real product (Vespignani et al , 2019; Gershon et al , 2019). Further, Odhiambo (2020) reviews the literature about the effect of oil price fluctuations on economic growth and he states that the effect varies for different countries or different samples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this instance, it is argued that oil price fluctuations have a considerable impact on individuals’ welfare over the globe (Mgbame et al , 2015). However, other works claim that the actions of economic policies can absorb the effect of oil price shocks on the real product (Vespignani et al , 2019; Gershon et al , 2019). Further, Odhiambo (2020) reviews the literature about the effect of oil price fluctuations on economic growth and he states that the effect varies for different countries or different samples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this example, it is contended that oil cost changes notably affect government agencies ability to assist its various economic sectors (Mgbame et al, 2015). Nonetheless, another different works guarantee that the activities of monetary arrangements can retain the impact of oil cost instabilities on the economic enhancement (Vespignani et al, 2019;Gershon et al, 2019). Further, Odhiambo (2020) suggested that the impact of oil cost instabilities on economic development varies between deferent countries based on their dependability on oil prices as a source of energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Mork et al (1989), there is asymmetry in economic policy and there are good reasons to believe this, so that whenever prices fall this is not met by inflationary policy in oil importing countries of the same magnitude. Researchers such as (Gershon et al, 2019;Vespignani et al, 2019) have claimed that the effects of oil price shocks on real product can be absorbed through the actions of economic policies. Also related to how oil price shocks influence economic policy is the aspect of uncertainty.…”
Section: Oil Price Fluctuations and Business Cycles: A Theoretical Fr...mentioning
confidence: 99%